Optimalisasi Jaringan Internet Sekolah dengan Fiber Optic, UTP Cat 6, dan VLAN - Sunaryo, Budi; Hamdi, Khairil; Rusydi, Muhammad Ilhamdi; Hazmi, Ariadi; Yuhefizar, Yuhefizar (Ikatan Ahli Informatika Indonesia, 2024)
The use of the internet in schools has become essential to support teaching and learning activities, but issues such as uneven network distribution and suboptimal performance often arise. This study aims to address these problems by implementing Fiber Optic, UTP Cat 6, and Virtual Local Area Network (VLAN) technologies to enhance the stability and speed of the school’s internet network. Using the Network Development Life Cycle (NDLC) method, which includes analysis, design, simulation, implementation, and monitoring phases, the study results showed a 30% increase in network throughput and a reduction in average latency by 15%. Additionally, the VLAN configuration successfully separated data traffic, improving the security and efficiency of the network. The network was able to support more than 1000 users with stable performance. In conclusion, the implementation of these technologies significantly optimized the school’s internet network and can serve as a technical guide for other schools seeking to improve their network quality.